Chevron Nails: A Normal Variant in the Pediatric Population. Issue 1 (22nd July 2013) - Delano, Sofia; Belazarian, Leah
Abstract A 7‐month‐old girl was evaluated for V‐shaped ridging of the fingernails consistent with chevron nails. Chevron nails are a normal variant in the pediatric population that is frequently outgrown. This case nicely demonstrates this normal finding that has so rarely been reported in the literature.